Comparison of the efficacy of latanoprost versus dorzolamide/timolol fixed combination therapy in patients with pseudoexfoliative glaucoma according to glaucoma stage - Sultan,Pinar (2022)
ABSTRACT Purpose: Only a few trials have compared the intraocular pressure-lowering effects of prostaglandin analogs to carbonic anhydrase inhibitor plus beta-blocker fixed-dose combination therapy in patients with pseudoexfoliative glaucoma. Furthermore, the influence of the glaucoma stage on the intraocular pressure-lowering effects of these drug types has not been studied. The purpose of this study was to compare the IOP-lowering efficacy of latanoprost, a prostaglandin analog versus dorzolamide/timolol fixed combination, a carbonic anhydrase inhibitor plus beta-blocker fixed-dose combination therapy, in patients with pseudoexfoliative glaucoma based on glaucoma stage. Methods: The data of 32 eyes (32 patients) diagnosed with uniocular pseudoexfoliative glaucoma and treated with topical latanoprost (Group 1) or dorzolamide/timolol fixed combination (Group 2) were retrospectively assessed. The groups were subdivided into early and moderate-advanced stages. Patients’ demographics, baseline intraocular pressure, final intraocular pressure, and intraocular pressure difference (the difference between the baseline and final intraocular pressure) were determined from medical records and compared between groups and according to glaucoma stage. Results: The mean drug use duration was 17.7 ± 13.5 months. No significant differences in mean baseline intraocular pressure, mean final intraocular pressure and mean intraocular pressure difference between Groups 1 and 2. In Group 2, the mean intraocular pressure difference was significantly greater in patients with early versus moderate-advanced stage glaucoma (p=0.015). The difference, however, was not detected in Group 1. The mean intraocular pressure difference in early-stage glaucoma was significantly greater in Group 2 versus 1 (p=0.033). Conclusions: Latanoprost and dorzolamide/timolol fixed combination are effective treatments for newly diagnosed pseudoexfoliative glaucoma. In early-stage pseudoexfoliative glaucoma, greater intraocular pressure reduction was noted with dorzolamide/timolol fixed combination than with latanoprost; thus, dorzolamide/timolol fixed combination should be considered when a significant decrease in intraocular pressure is desired in early-stage glaucoma.